Protective effect of melatonin as an antioxidant in the intestine of rats with superior mesenteric arterial occlusion - Yuan, Xiaoqiang; Xi, Zhang; Yu, Bailong- (Cellular and Molecular Biology, 2022)
The superior mesenteric artery is a branch of the aortic artery that supplies blood to the small and some parts of the large intestine. Any obstruction in blood flow and reperfusion causes tissue damage in the intestine. This study aimed to determine the rate of fat peroxidation and tissue protein as an indicator of tissue degradation after ischemia and reperfusion following induction of superior mesenteric artery occlusion in the intestine and to evaluate the protective effect of melatonin as a free radical scavenger and antioxidants in rats. In this study, 36 male Wistar-Albino rats weighing between 80-120 g were equally divided into six groups and received different melatonin doses (10, 20, and 30 mg/kg) intramuscularly. In this regard, Group 1 was the control group, Group 2 was the Sham group (underwent surgery to dissect the upper mesenteric artery and injected the same volume of solvent), Group 3 was Ischemia-reperfusion (IR), Group 4 was IR with melatonin at a dose of 10 mg/kg, Group 5 was IR with melatonin at a dose of 20 mg/kg, and Group 6 was IR with melatonin at a dose of 30 mg/kg. The results showed that the level of tissue malondialdehyde (MDA) was significantly lower in groups 4, 5, and 6 than in group 3 (P <0.05). Tissue protein levels were significantly higher in group 4 than in group 3 (P <0.001). Tissue protein levels in groups 5 and 6 did not significantly differ from group 3 (P = 0.191). Overall, this study showed that melatonin at a dose of 10 mg/kg has an antioxidant effect preventing induced damage due to superior mesenteric artery occlusion.